Método e metafísica em Edith Stein: via agostiniana e via aristotélica no procedimento investigativo de ascensão ao sentido do ser - Rocha, Rafael Carneiro (2016)
The book Endliches und Ewiges Sein (Finite and Eternal Being), by Edith Stein, has in its own subtitle the exposition of its purpose:“Versuch eines Aufstiegs zum Sinn des Seins” (which can be translated as “An Attempt at an Ascent to the meaning of being”). Although the author's starting point for her inquiry about the sense of being is phenomenological, from the fact of the being of the ego - after all, as she herself asserts, her mother tongue is philosophically the language of Husserl - the way of the certainty of the ego (which she calls “augustinian”) occurs in the context of her work together with the way that she calls “aristotelian”, which proceeds from what is intrusive to us [Aufdrängenden] by first, namely, the world of the sensibly perceived things. Despite the apparent antagonism, the author argues that the Augustinian and the Aristotelian ways must complement each other. The philosophical project of Edith Stein, as the author herself emphasizes at the beginning of Potenz und Akt (Potency and Act), should be considered an “ontology” or a science of being, because if we do not understand what is being, we do not understand anything. On the other hand, the transcendental perspective recommends itself as an initial approach because it proposes a consideration of the origin of the meaning of all being, describing the structures of consciousness in which an by which the transcendent world is constructed from immanence. This means that without the transcendental perspective, the ontology remains inexplicable and its constitutive problems are all neglected. However, Edith Stein gives a certain preeminence to the augustinian way, which starts from the life of the ego [Ichleben]. Such preeminence s due to the fact that it is in the realm of the life of the ego that reality itself gains meaning as reality. In this way, the essentialites occupy an eminent position, because just them carry with themselves the possibility of being fully intelligible, thus transmiting intelligibility and meaning to the objects of reality. The book Endliches und Ewiges Sein (Finite and Eternal Being), by Edith Stein, has in its own subtitle the exposition of its purpose:“Versuch eines Aufstiegs zum Sinn des Seins” (which can be translated as “An Attempt at an Ascent to the meaning of being”). Although the author's starting point for her inquiry about the sense of being is phenomenological, from the fact of the being of the ego - after all, as she herself asserts, her mother tongue is philosophically the language of Husserl - the way of the certainty of the ego (which she calls “augustinian”) occurs in the context of her work together with the way that she calls “aristotelian”, which proceeds from what is intrusive to us [Aufdrängenden] by first, namely, the world of the sensibly perceived things. Despite the apparent antagonism, the author argues that the Augustinian and the Aristotelian ways must complement each other. The philosophical project of Edith Stein, as the author herself emphasizes at the beginning of Potenz und Akt (Potency and Act), should be considered an “ontology” or a science of being, because if we do not understand what is being, we do not understand anything. On the other hand, the transcendental perspective recommends itself as an initial approach because it proposes a consideration of the origin of the meaning of all being, describing the structures of consciousness in which an by which the transcendent world is constructed from immanence. This means that without the transcendental perspective, the ontology remains inexplicable and its constitutive problems are all neglected. However, Edith Stein gives a certain preeminence to the augustinian way, which starts from the life of the ego [Ichleben]. Such preeminence s due to the fact that it is in the realm of the life of the ego that reality itself gains meaning as reality. In this way, the essentialites occupy an eminent position, because just them carry with themselves the possibility of being fully intelligible, thus transmiting intelligibility and meaning to the objects of reality.